(untitled) (Global Journal of Management and Business Research, 2022)
The overarching goal of this study was to investigate the use of social networking sites in Kano manufacturing organizations and their impact on employee productivity, with a particular focus on HNL Manufacturing Company Kano. The study aimed to accomplish the following goals: to identify the use of social media networks in Kano manufacturing organizations; to investigate the impact of social networking sites on employee productivity at HNL Manufacturing Company; and to identify techniques that manufacturing organizations can use to increase employee productivity through social media networks. The analysis used a sample random sampling technique to implement a descriptive research design. The data collection method was carried out at HNL Company via an interview with a targeted sample size of 26 employees. The key findings of the study indicate that considering the limitations and nature of social media policies, workers accessed social media once a day on their devices for more than 2 hours at work and discovered that HNL Manufacturing Company had adopted different techniques such as crowdsourcing, enterprise social networks to some degree and Facebook Fridays that are not in use. The report also concludes that social media has a very modest effect on the efficiency of employees. Research advises that manufacturing companies do not neglect using different social media techniques and policies. It is no longer realistic or feasible to enforce a complete moratorium on accessing social networking sites at work. Every week, social networking websites are developed. It would be a boring and never-ending job to block access to any social networking website.